A 2D electrocardiogram data compression method using a sample entropy-based complexity sorting approach. (November 2016) - Pandey, Anukul; Saini, Barjinder Singh; Singh, Butta; Sood, Neetu
Highlights: Exploitation of inter and intra beat correlation for 2D ECG data compression. A progressive pre-processing techniques to foster the uniformity in 2D ECG array. Quasi-periodic ECG compression using entropy based nonlinear complexity sorting. Proposed method outperforms the variance based linear complexity sorting approach. Abstract: This paper proposes an effectual sample entropy (SampEn) based complexity sorting pre-processing technique for two dimensional electrocardiogram (ECG) data compression. The novelty of the approach lies in its ability to compress the quasi-periodic ECG signal by exploiting the intra and inter-beat correlations. The proposed method comprises the following steps: (1) QRS detection, (2) Length normalization, (3) Dc equalization, (4) SampEn based nonlinear complexity sorting and (5) Compression using JPEG2000 Codec. The performance has been evaluated over 48 records from the MIT-BIH arrhythmia database. The average quality score (QS) measurements at different residual errors were 42.25, 4.73, and 2.75 for percentage root mean square difference (PRD), PRD1024, and PRD Normalized respectively. The work also reports extensive experimentations on the compressor for various durations of the ECG records (5–30 min, with 5-min increment). The proposed algorithm demonstrates significantly better performance in comparison to the contemporary state-of-the-art works present in the literature. Graphical abstract: